Heterosis and Combining Ability of Maize (Zea mays L.) Grain Protein, Oil and Starch Content and Yield as Affected by Water Stress - , A. M. M. Al-Naggar; , M. M. M. Atta; , M. A. Ahmed; , A. S. M. Younis (Archives of Current Research International, 2016)
Information on heterosis and combining ability of available germplasm would help maize breeder in identifying proper genotypes and breeding procedures for improving tolerant varieties to water stress. The objective of this investigation was to assess the performance, heterobeltiosis, general combining ability (GCA) and specific combining ability (SCA) for grain quality and yield traits among inbred lines of maize under water stress (WS) and well watering (WW) conditions. Six inbred lines of maize differing in drought tolerance and their diallel F1 crosses were evaluated in 2013 and 2014 seasons, in two separate experiments; one under WW and one under WS. In most cases, heterobeltiosis under WS was higher than WW. The GCA (additive) variance was higher than SCA (non-additive) variance for grain protein content (GPC) and/or grain oil content (GOC) and grain starch content (GSC) under WS, but the opposite was true for the rest of traits. Under WS, there were significant correlations between inbred mean and GCA effects for GPC, grain yield/plant (GYPP), grain yield/ha (GYPH), protein yield/ha (PYPH) and starch yield/ha (SYPH), between hybrid mean and SCA effects for GYPP, GYPH, PYPH and SYPH, between hybrid mean and heterobeltiosis for GPC, GOC and GSC and between SCA effects and heterobeltiosis for GOC only. The breeding method of choice is selection for improving GPC, GOC and GSC, and heterosis for GYPP, GYPH, PYPH, OYPH and SYPH. Mean performance for yield traits of a given inbred and hybrid could be considered as an indication of its GCA and SCA effects, respectively.